Strategy for the development of agricultural machinery: importance of patent analysis - Silveira, Franco da; Machado, Filipe Molinar; Romano, Leonardo Nabaes; Amaral, Fernando Gonçalves; Ruppenthal, Janis Elisa (Brazilian Journal of Operations & Production Management, 2018)
During the product development, patents help identify new project opportunities and, if well analyzed, can reveal technical strategies in terms of how countries, companies, and universities link patents and product development. In the context of the agricultural machinery sector there is a complexity in the integration of data from patents with the stages of development conceptions. In this context, the article aims to present how the information obtained from a patent bank can be used for the development of agricultural machinery. As a methodology, the Systematic Bibliographic Review was selected to identify and relate strategies that add value throughout the agricultural machinery project. As a result, research has shown that the use of patent information can assist in the development of agricultural machinery from technical data. In addition, patents are characterized as a valuable source of technological information, as it is inexpensive and capable of feeding a company in its own research activity and in the development of new products. It is concluded that the information from patents, suggested as strategies in the model of agricultural machinery development, allows for managerial and technical decisions aimed at improving products. Finally, the research contributed to fill the information gap between patents and the development of agricultural machinery, a diffusion of data that, if well connected, can promote a competitive differential in companies.